Comparison of Clevidipine Versus Sodium Nitroprusside for the Treatment of Postoperative Hypertension in Cardiac Surgery Patients - Freiberger, Natalie A. (Hosp Pharm, 2016)
OBJECTIVE: To evaluate the efficacy and safety of clevidipine (CLV) versus sodium nitroprusside (SNP) for the treatment of hypertension (HTN) in postoperative cardiac surgery patients at a community hospital. METHODS: This single-center, retrospective, cohort study included cardiac surgery patients treated with CLV or SNP for postoperative systolic blood pressure (SBP) control. The primary efficacy outcome was defined as the mean number of times the SBP rose above 140 mm Hg. Secondary outcomes included a comparative cost analysis and a safety analysis. RESULTS: Forty patients were included in each arm. Patients who received CLV had a higher incidence of SBP readings greater than 140 mm Hg (p < .05). There were no differences in safety outcomes, number of patients who received as-needed (PRN) antihypertensives, or mean number of PRN antihypertensives required. There were differences in infusion duration (22.4 hours CLV vs 15.6 hours SNP; p = .035), number of infusions dispensed (2.8 CLV vs 1.3 SNP; p = .001), and length of hospital stay (12.33 days CLV vs 7.65 days SNP; p = .013). However, CLV was less expensive based on the AWP cost at the time of review. CONCLUSIONS: Although a difference in blood pressure control was seen between CLV and SNP, the safety profiles were similar between the 2 drugs. In addition, CLV remained less expensive than SNP for postoperative BP control.